2013
DOI: 10.1007/s40122-013-0009-8
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Study of Pregabalin in Patients with Cancer-Induced Bone Pain

Abstract: IntroductionImprovements are needed in the management of cancer-induced bone pain (CIBP). The objective of this study was to assess the efficacy and safety of pregabalin compared with placebo in the adjunctive treatment of patients with moderate to severe CIBP who were receiving opioids.MethodsIn this randomized, double-blind, placebo-controlled, parallel-group, multicenter trial, 152 adults diagnosed with a malignant, solid tumor with metastases to bone were randomized to flexible-dose pregabalin (100, 150, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 28 publications
0
28
0
4
Order By: Relevance
“…14 It was followed by a randomized trial of pregabalin versus placebo, which suggested potential value of pregabalin in CIBP, although firm conclusions could not be drawn. 15 Another study suggested pregabalin in combination with mirtazapine may be beneficial; however, it advised additional trials. 16 Nevertheless, despite the limited evidence, pregabalin is often prescribed for CIBP, with some reviews of CIBP management recommending the use of pregabalin if there is a neuropathic component to the pain.…”
Section: Discussionmentioning
confidence: 99%
“…14 It was followed by a randomized trial of pregabalin versus placebo, which suggested potential value of pregabalin in CIBP, although firm conclusions could not be drawn. 15 Another study suggested pregabalin in combination with mirtazapine may be beneficial; however, it advised additional trials. 16 Nevertheless, despite the limited evidence, pregabalin is often prescribed for CIBP, with some reviews of CIBP management recommending the use of pregabalin if there is a neuropathic component to the pain.…”
Section: Discussionmentioning
confidence: 99%
“…One RCT that compared the efficacy of pregabalin vs. placebo in patients with metastatic bone pain was aborted because of slow inclusion. The pain in the pregabalin group seemed to decrease more than in the placebo group.…”
Section: Resultsmentioning
confidence: 99%
“…Adjuvant analgesics in the treatment of cancer pain are usually, but not exclusively, used for the treatment of purely neuropathic or mixed cancer pain. Anticonvulsants and antidepressants are increasingly used for pain due to bone metastases, and NMDA receptor antagonists are mainly used when other therapies fail …”
Section: Discussionmentioning
confidence: 99%
“…8 Gabapentin is also known to increase the serotonin concentration in human blood, which may be linked to its neurobehavioral actions. 14 Krane and Heller 4 observed the natural history of PLP in pediatric patients who underwent amputation and found that both frequency and intensity of PLP were decreased within six months after amputation, and the rate of PLP remained unchanged significantly after six months to seven years. For patients who did not develop postoperative PLP, gabapentin can be discontinued six weeks after amputation.…”
Section: Discussionmentioning
confidence: 99%